Crude unit corrosion guide : a manual for plant operators, process engineers, metallurgists, maintenance engineers, inspectors, and equipment specialists - Gutzeit, Joerg (NACE International, 2016)
This Guide was written for Plant Operators, Process Engineers, Metallurgists, Maintenance Engineers, Inspectors, and all others who deal with crude unit corrosion and fouling issues on a daily basis. The book is based on the author's experience dealing with many crude units and also reflects the Industry's consensus experiences reported at past meetings of the NACE STG34 Committee on Petroleum Refining and Gas Processing and the API Subcommittee on Corrosion and Materials. Diluent recovery units (DRUs) and vacuum distillation units (VDUs) of bitumen upgraders are now included in the discussions where appropriate. While process simulation and RBIM software has been very helpful for ranking critical components for future inspection and maintenance efforts, expertise is still required to facilitate reliable data input and assessment. This book presents the most important aspects of corrosion and fouling control in the atmospheric and vacuum sections of crude units and the corresponding sections in bitumen upgraders.